2018
DOI: 10.1186/s12985-018-1015-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of commercial IgM and IgG enzyme-linked immunoassays (ELISAs) for diagnosis of Zika virus infection

Abstract: BackgroundSerologic detection of Zika virus (ZIKV) infections is challenging because of antigenic similarities among flaviviruses.ObjectiveTo evaluate the sensitivity and specificity of commercial ZIKV IgM and IgG enzyme-linked immunoassay (ELISA) kits.MethodsWe used sera from febrile patients with RT-PCR-confirmed ZIKV infection to determine sensitivity and sera from RT-PCR-confirmed dengue cases and blood donors, both of which were collected before ZIKV epidemics in Brazil (2009–2011 and 2013, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 24 publications
4
42
1
4
Order By: Relevance
“…This may be explained by our limited capacity for detecting ZIKV infections among the general patient population seeking medical care at the health unit because our inclusion criteria required the presence of fever, which is less common in ZIKV infections [19]. In addition, the sensitivity of ZIKV molecular diagnosis is limited [20], hampering case detection during the viremic phase of the infection, and we did not employ ZIKV serological tests due to their low accuracy [13,14]. Finally, some patients diagnosed with an acute FLAV infection based on DENV IgM-ELISA seroconversion might actually have reflected a ZIKV infection that cross-reacted with DENV.…”
Section: Temporal Distribution Of Arboviral Infectionsmentioning
confidence: 99%
“…This may be explained by our limited capacity for detecting ZIKV infections among the general patient population seeking medical care at the health unit because our inclusion criteria required the presence of fever, which is less common in ZIKV infections [19]. In addition, the sensitivity of ZIKV molecular diagnosis is limited [20], hampering case detection during the viremic phase of the infection, and we did not employ ZIKV serological tests due to their low accuracy [13,14]. Finally, some patients diagnosed with an acute FLAV infection based on DENV IgM-ELISA seroconversion might actually have reflected a ZIKV infection that cross-reacted with DENV.…”
Section: Temporal Distribution Of Arboviral Infectionsmentioning
confidence: 99%
“…Since the ZIKV outbreak in the Northeast of Brazil, there was a major effort towards the development of a reliable serological test. For other flavivirus, particularly DENV, the laboratory diagnostic was mostly based on the detection of antibodies against the non-structural protein 1, NS1 (Kikuti et al 2018;Stettler et al 2016). Previous work indicated that serological assays based on NS1 can be used to discriminate ZIKV and DENV infections (Balmaseda et al 2017;Bosch et al 2017;Stettler et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, ZIKV and DENV proteins share high sequence identity resulting in the cross-reactivity of antibodies generated after the infection (Balmaseda et al 2017;Fernanda Estofolete et al 2016;Granger et al 2017;Priyamvada et al 2017). In spite of significant progress made in the last years in our understanding of ZIKV, the improvement of diagnostic assays is still needed (Kikuti et al 2018;Theel and Hata 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To this extent, we can only report that patients had some type of arbovirus, but cannot determine whether it was chikungunya, dengue, or Zika virus. Differential diagnosis of Flavivirus species is complicated because commercial tests for dengue virus cross‐react to Zika virus antibodies and vice versa …”
Section: Discussionmentioning
confidence: 99%